Evaluation of the efficacy of humic acids to counteract the toxic effects of aflatoxin B1 in turkey poults - Maguey-González, Jesús Adonai; Nava-Ramírez, María de Jesús; Gómez-Rosales, Sergio; Ángeles, María de Lourdes; Solís-Cruz, Bruno; Hernández-Patlán, Daniel; Merino-Guzmán, Rubén; Hernandez-Velasco, Xochitl; Hernández-Ramírez, Juan Omar; Loeza, Ileana; Senas-Cuesta, Roberto; Latorre, Juan D.; et al. (Frontiers in Veterinary Science, 2023)
This study aims to evaluate the efficacy of humic acid (HA) from worm compost as an adsorbent for aflatoxin B1 (AFB1) in turkey poults. The experiment involved the inclusion of 0.25% (w/w) HA in the diet of turkey poults consuming aflatoxin-contaminated feed (250 ng AFB1/g). A total of 350 1-day-old female Nicholas-700 turkey poults were randomly allocated to five equal groups: negative control (basal diet); positive control (basal diet + 250 ng AFB1/g; HA (basal diet + 0.25% HA); HA + AFB1 (basal diet + HA + 250 ng AFB1/g); and zeolite + AFB1 (basal diet + 0.25% zeolite + 250 ng AFB1/g). Each group had seven replicates of 10 poults (n = 70). The impact of HA addition was evaluated in terms of performance parameters, relative organ weights, liver histological lesions, and serum biochemical and hematological constituents. In general, the addition of HA improved body weight (BW), body weight gain (BWG), and feed conversion rate (FCR). Furthermore, HA effectively mitigated the toxic effects caused by AFB1 in the majority of the analyzed variables. The results indicated that HA effectively counteracted the AFB1-induced toxic effects in turkey poults. Based on these findings, it can be concluded that HA is capable of removing AFB1 from the contaminated diet.